Enhancing the tolerance of Clostridium saccharoperbutylacetonicum to ligno‐ cellulosic-biomass-derived inhibitors for efficient biobutanol production by overexpressing efflux pumps genes from Pseudomonas putida - Jiménez Bonilla, Pablo (2020)
Furan aldehydes and phenolic compounds generated during biomass pretreatment can inhibit fermentation for biofuel production. Efflux pumps actively transport small molecules out of cells, thus sustaining normal microbial metabolism. Pseudomonas putida has outstanding tolerance to butanol and other small molecules, and we hypothesize that its efflux pump could play essential roles for such robustness. Here, we overexpressed efflux pump genes from P. putida to enhance tolerance of hyper-butanol producing Clostridium saccharoperbutylacetonicum to fermentation inhibitors. Interestingly, overexpression of the whole unit resulted in decreased tolerance, while overexpression of the subunit (srpB) alone exerted significant enhanced robustness of the strain. Compared to the control, the engineered strain had enhanced capability to grow in media containing 17% more furfural or 50% more ferulic acid, and produced ~14 g/L butanol (comparable to fermentation under regular conditions without inhibitors). This study provided valuable reference for boosting microbial robustness towards efficient biofuel production from lignocellulosic materials.